Process evaluation of a parenting program for low-income families in South Africa - Lachman, JM; Kelly, J; Cluver, L; Ward, CL; Hutchings, J; Gardner, F (SAGE Publications, 2016)
Objective: This mixed-methods process evaluation examined the feasibility of a parenting program delivered by community facilitators to reduce the risk of child maltreatment in low-income families with children aged 3–8 years in Cape Town, South Africa (N = 68).